A coordinated voltage support strategy for LV network with multiple DSTATCOMs - Mokhtari, G.; Nourbakhsh, G.; Ghosh, Arindam (Institute of Electrical and Electronics Engineers ( IEEE ), 2013)
Voltage rise and drop are the main power quality challenges in Low Voltage (LV) network with Renewable Energy (RE) generators. This paper proposes a new voltage support strategy based on coordination of multiple Distribution Static Synchronous Compensators (DSTATCOMs) using consensus algorithm. The study focuses on LV network with PV as the RE source for customers. The proposed approach applied to a typical residential LV network and its advantages are shown comparing with other voltage control strategies.